PENGARUH PEMBERIAN EKSTRAK ZAT PEDAS RIMPANG JAHE EMPRIT YANG DISARI DENGAN ETANOL 70% TERHADAP FAGOSITOSIS MAKROFAG PADA MENCIT JANTAN YANG DIINFEKSI DENGAN Listeria monocytogenes - Dyah Mellawati; Sudarsono Sudarsono; Agustinus Yuswanto (Majalah Obat Tradisional, 2010)
Immunomodulator has been used as one of the attention to develop herbal medicine. Jahe is one of herbal medicine which is usually used to heal various diseases. Jahe Emprit  is one of local name of Jahe in Indonesia. The aim of this research was to investigate the effect of pungent principle containing extract of Jahe emprit rhizome on the macrophage activity compared by levamisol and Echinacea extract. Extraction was done by 70%v/v ethanol. The concentrations of extract were 5 mg/kg B.W; 25 mg/kg B.W; and 100 mg/kg B.W. CMC Na 1,5%w/v was used as solvent control. Levamisol 2,5 mg/kg B.W and Echinacea extract 10 mg/kg B.W were used as positive control. The macrophage ability  were measured according to Leijh et al., (1986) that was basically on the amount of latex which was captured  by macrophage. The extracts were orally administrated to the Swiss male mice at the dose of 0,2 ml/20 g B.W. The Macrophage  activity was analyzed by one way ANOVA at 95% of confidence level. The extract which had specification of 35% relative concentration of pungent principles; 3,554% ± 0,145 % W/W total phenolic substances; 13,70 mg/ml  antioxydative value  (IC50) at the concentrations of  5 mg/kg B.W and 25 mg/kg B.W could increase phagocytosis  ability. The ability of the extract at the concentration 25 mg/kg.B.W had no different with either the Levamizol 2,5 mg/kg. B.W., and Echinacea extract 2,5 mg/kg. B.W.